Surface modification of medical grade biomaterials by using a low-temperature-processed dual functional Ag-TiO2 coating for preventing biofilm formation - Pradhan L.; Hazra S.; Singh S.V.; Bajrang N.; Upadhyay A.; Pal B.N.; Mukherjee S. (My University, 2025)
Biofilm development in medical devices is considered the major virulence component that leads to increased mortality and morbidity among patients. Removing a biofilm once formed is challenging and frequently results in persistent infections. Many current antibiofilm coating strategies involve harsh conditions causing damage to the surface of the medical devices. To address the issue of bacterial attachment in medical devices, we propose a novel antibacterial surface modification approach. In this paper, we developed a novel low-temperature based solution-processed approach to deposit silver nanoparticles (Ag NPs) inside a titanium oxide (TiO2) matrix to obtain a Ag-TiO2 nanoparticle coating. The low temperature (120 °C)-based UV annealed drop cast method is novel and ensures no surface damage to the medical devices. Various medical-grade biomaterials were then coated using Ag-TiO2 to modify the surface of the materials. Several studies were performed to observe the antibacterial and antibiofilm properties of Ag-TiO2-coated medical devices and biomaterials. Moreover, the Ag-TiO2 NPs did not show any skin irritation in rats and showed biocompatibility in the chicken egg model. This study indicates that Ag-TiO2 coating has promising potential for healthcare applications to combat microbial infection and biofilm formation. © 2024 The Royal Society of Chemistry.